Praktik Pengenalan Lapangan terhadap Observasi Fisik di RA Al-Fajar Kec. Medan Denai Kab. Deli Serdang - Ramadhani, Ainun Qolbu; Lubis, Ainun Ramdhani; Harahap, Nurul Hafifah; Aminah, Siti; Lutfhi, Mukhyar; Ketaren, Yogi Karmelta; Marpaung, Zulham Efendi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This article discusses the practice of field recognition of physical observation at RA Al Fajar. This school is located in a strategic location to support the creation of good teaching and learning activities. RA Al-Fajar is a school that really maintains cleanliness, neatness, and order in carrying out administration in the learning process. There are 6 teachers at RA Al-Fajar, while 11 students are available in one class only. The facilities and infrastructure at this school are very decent and good. The learning and teaching activities are also in accordance with the education units based on the Permendiknas, namely using the learning implementation plan (RPP). This study aims to find out the conditions and circumstances that occur in the field of RA Al-Fajar related to infrastructure and teaching and learning activities. The method in this study is a qualitative research method with observation data collection instruments. The results of this study RA Al-Fajar is a school with very good infrastructure and teaching and learning activities. The infrastructure provided is in accordance with the learning needs of children. The curriculum is implemented in accordance with Permendikbud standards. As well as teaching and learning activities are also in accordance with the standards of the learning process Keywords: Physical observation of learning, infrastructure, teaching and learning activities